IMPLICATION OF PRINCIPLES IN THE INTERNATIONAL CONVENTION ON THE PROTECTION OF THE RIGHTS OF MIGRANT WORKERS AND MEMBERS OF THEIR FAMILIES IN LAW NO. 18 OF 2017 IN AN EFFORT TO PROTECT INDONESIAN MIGRANT WORKERS ABROAD - Muhammad Iqbal; Fifik Wiryani (Universitas Muhammadiyah Malang, 2020)
The imbalance between the number of labor force and the number of jobs makes employment opportunities abroad one of solution to reduce unemployment. Indonesia has established regulations relating to the placement of Indonesian Migrant Workers through Law Number 18 of 2017 concerning Protection of Indonesian Migrant Workers. Meanwhile, long before the formation of this law, an international agreement was made regarding the protection of migrant workers and their families through the International Convention On The Protection Of The Rights Of All Migrant Workers And Members Of Their Families which was initiated on 18 December 1990 in New York, United States. In this research, an assessment of Law no. 18 of 2017 concerning the Protection of Indonesian Migrant Workers against compliance with the principles contained in the International Convention On The Protection Of The Rights Of All Migrant Workers And Members Of Their Families was carried out. From the research, it is found that the Convention has been able to influence the legal norms in Law no. 18 of 2017 with the strengthening of human values through the principles and the existence of Indonesian Migrant Workers rights which do not only regulate Indonesian Migrant Workers themselves but also related to their family rights.